Association of Preterm Birth With Risk of Ischemic Heart Disease in Adulthood - Crump, Casey (JAMA Pediatr, 2019)
IMPORTANCE: Preterm birth has previously been associated with increased risks of hypertension and diabetes, but not ischemic heart disease (IHD), in adulthood. The reasons for this lack of association with IHD despite associations with its risk factors have been elusive, but may be associated with methodologic issues, such as survivor bias, in prior studies. OBJECTIVE: To determine whether preterm birth is associated with an increased risk of IHD in adulthood in a large population-based cohort. DESIGN, SETTING, AND PARTICIPANTS: This national, population-based cohort study included all 2 141 709 persons who were born as singleton live births in Sweden during 1973 to 1994. The data were analyzed in September 2018. EXPOSURES: Gestational age at birth, identified from nationwide birth records in the Swedish Birth Registry. MAIN OUTCOMES AND MEASURES: Ischemic heart disease that was identified from nationwide inpatient and outpatient diagnoses through 2015 (maximum age, 43 years). A Cox regression was used to examine gestational age at birth in association with IHD in adulthood while adjusting for other perinatal and maternal factors. Cosibling analyses assessed for potential confounding by unmeasured shared familial factors. RESULTS: Of 2 141 709 participants, 1 041 906 (48.6%) were female and there were 1921 persons (0.09%) who received a diagnosis of IHD in 30.9 million person-years of follow-up. Gestational age at birth was inversely associated with IHD risk in adulthood. At ages 30 to 43 years, adjusted hazard ratios for IHD associated with preterm (gestational age <37 weeks) and early-term birth (37-38 weeks) were 1.53 (95% CI, 1.20-1.94) and 1.19 (1.01-1.40), respectively, compared with full-term birth (39-41 weeks). Preterm-born women had lower IHD incidence than preterm-born men (15.16 vs 22.00 per 100 000 person-years) but had a higher adjusted hazard ratio (1.93; 95% CI, 1.28-2.90 vs 1.37; 95% CI, 1.01-1.84). These associations did not appear to be explained by shared genetic or environmental factors in families. CONCLUSIONS AND RELEVANCE: In this large national cohort, preterm and early-term birth were associated with an increased IHD risk in adulthood. Persons born prematurely need early evaluation and preventive actions to reduce the risk of IHD.